Semantic Functions Of Reduplication In English And Uzbek Languages - Begimkulova Dilobar Bakhtiyor kizi (Euro Asian Journal Publishing, 2024)
This article discusses semantic functions of reduplication in English and Uzbek languages. Drawing on a comprehensive analysis of linguistic studies and examples from various sources, the research investigates various semantic aspects of reduplication across world languages and examines 16 prominent semantic functions in English and Uzbek languages. The insights in the article pave the way for a deeper comprehension of the dynamic and multifaceted nature of reduplication in diverse linguistic landscapes.
Keywords: reduplication; semantic functions; plurality